Overly reliant on central bank funding? Consequences of exiting TLTRO - Florian Heider; Jonas Schlegel (Leibniz Institute for Financial Research SAFE, 2024)
This study analyses potential consequences of exiting the Targeted Long-Term Refinancing Operations (TLTRO) of the European Central Bank (ECB). Thanks to its asset purchase programs, the Eurosystem stillholds plenty of reserveseven with a full exit from the TLTROs. This explains why voluntary and mandatory repayments of TLTRO III borrowing went smoothly. Nevertheless, the more liquidity is drained from the banking system, the more important becomes interbank market borrowing and lending, ideally between euro area member states. Right now, the usual fault lines ofthe euro area show up. The German banking system has plenty of reserves while there are first signs of aggregate scarcity in the Italian banking system. This does not need to be a source of concern if the interbank market can be sufficiently reactivated. Moreover, the ECB has several tools to address possible future liquidity shortages. This document was provided/prepared by the Economic Governance and EMU scrutiny Unit at the request of the ECON Committee.
Keywords: 330